Reaction of tomato (Solanum lycopersicum) genotypes for resistance to late blight (Phytophthora infestans) disease - SOLANKEY, S S; AKHTAR, SHIRIN; NEHA, PALLAVI; RAY, P K; SINGH, RAVI GOPAL (The Indian Journal of Agricultural Sciences, 2017)
The cultivated tomato (Solanum lycopersicum L.) is affected by several of diseases of which late blight, caused by Phytophthora infestans ((Mont.) de Bary), being the most severe under epidemic condition. Wild tomato species have proven as continuing source of resistance to this disease. The reaction of 152 tomato genotypes including 4 wild relatives, i.e. Solanum chilense, S. pimpenellifolium, S. cheesmaniae, S. peruvianum, against late blight was determined using whole-plant scoring. These genotypes were screened and evaluated in two different conditions (open field and side open poly house) at the Department of Horticulture (Vegetable and Floriculture), Bihar Agricultural University, Sabour, Bhagalpur (Bihar) in autumn-winter season of 2013-14. Of the 152 genotypes, none of the testgenotypes showed immune reaction. Moreover, the genotypes Arka Rakshak, Arka Alok, BRDT-1, Kashi Anupam, Arka Ananya, Azad T-5, C 6 T and Kashi Vishesh high yield potential and lower incidence for late blight. Moreover, wild species S. chilense, S. pimpenellifolium, S. cheesmaniae and S. peruvianum showed resistance reaction for late blight. The genotype EC 538380 showed highly resistant disease reaction against late blight besides bearing more fruits. Moreover, significant effect of temperature and relative humidity was established on occurrence late of blight. In general cool, wet, cloudy weather with rainfall and ambient relative humidity favour late blight development andnatural epidemics of P. infestans in the field which can be useful in screening large populations. The highest disease infestation and severity occurred during the month of January – February when the maximum temperature ranged from 10.4–10.8°C and maximum relative humidity ranged from 90 – 95%.